2008
DOI: 10.1039/b805595e
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic applications of carbolithiation transformations

Abstract: Carbolithiation reactions are exceptionally versatile transformations which have been utilised in a remarkably diverse and creative manner. In this review we outline the background and scope of these reactions and then focus on their use in organic synthesis with a particular emphasis on literature examples published since 2000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 98 publications
2
32
0
2
Order By: Relevance
“…1). The stereochemical outcome of the reaction is consistent with syn -addition of the organolithium across the double bond (as is typical for carbolithiation [9,19]) followed by retentive protonation.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…1). The stereochemical outcome of the reaction is consistent with syn -addition of the organolithium across the double bond (as is typical for carbolithiation [9,19]) followed by retentive protonation.…”
Section: Resultssupporting
confidence: 53%
“…However, we [34] and others [57] have shown that this typical reactive polarity may be reversed when N -acylenamines (especially N -vinyl ureas [8]) meet organolithium nucleophiles. N -Carbamoyl enamines bearing α-aryl substituents (in other words, α-acylaminostyrenes), may undergo reaction as electrophiles, with the carbon atom β to nitrogen succumbing to attack by organolithium nucleophiles in an enamine carbolithiation reaction [9]. Similar reactivity is observed with related O -carbamoyl enols [1012].…”
Section: Introductionmentioning
confidence: 99%
“…The challenging problem of intermolecular carbolithiation reactions of alkenes led to the development of creative solutions. One approach among others is to control the intermolecular carbolithiation of alkenes by choosing suitable substrates bearing proximal chelating moieties capable of stabilizing the newly formed organolithium intermediates [5,6]. This approach has been combined with the use of external chiral ligands for the asymmetric addition of organolithium reagents.…”
Section: Intermolecular Carbolithiation Of Alkenesmentioning
confidence: 99%
“…Such species can, in turn, trap an electrophile and afford tetrasubstituted olefins, often in a stereocontrolled manner 2. In the case of the carbolithiation, the counterintuitive addition of a nucleophilic organometallic onto an already electron‐rich triple bond works thanks to the Lewis acid character of the metallic counterion 2f–g. Thus, highly polarized organolithiums provide simultaneously the triple bond activation and the reactive nucleophile, in contrast to neutral nucleophiles, which require an external activator such as the ynophile gold or platinum cations.…”
Section: Introductionmentioning
confidence: 99%